Preliminary Analysis of Safety and Feasibility of a Single-Hole Laparoscopic Myomectomy via an Abdominal Scar Approach - Tang, Huimin; Dong, Zhiyong; Qin, Zhenyue; Zhang, Shoufeng; Wang, Huihui; Wei, Weiwei; Shi, Ruxia; Chen, Jiming; Xia, Bairong (Frontiers in Surgery, 2022)
Purpose:To explore the safety and feasibility of single hole laparoscopic myomectomy through abdominal scar approach. Method:The clinical data of 7 patients who underwent single hole laparoscopic myomectomy via abdominal scar approach from January 2021 to November 2021 in Department of Gynecology, the Affiliated Changzhou No. 2 People's Hospital of Nanjing Medical University, were studied retrospectively,The duration of operation, the amount of intraoperative bleeding, the decrease of postoperative hemoglobin and the postoperative visual analog score (0 point no pain, 10 points maximum pain) were recorded. Results:The average blood loss was (101.42 ± 7.89) ml, the average length of hospital stay was (5 ± 0.53) days, the average operation time was (130 ± 26.86) min, and the 24-hour pain score was less than 2, 7 patients had no intraoperative or postoperative complications, and did not hurt the ureter and bladder. All patients could urinate spontaneously without urinary retention or urinary tract infection after catheter removal. No analgesic drugs were used after operation. Conclusion: Laparoscopic single-site hysteromyoma removal through abdominal wall scar approach is a more aesthetic and feasible option for eligible patients, but more cases and studies are needed for further confirmation.